Advancements in technology for the diagnosis and treatment of gastric cancer: A narrative review.: Gastric Cancer - Vadhavekar, Nidhi; Kaur, Deepinder; Pannu, Vanshika; Shafi, Nabahat; Sawant, Yuvraj; Latkar, Aarya; Pandya, Manu; Shahnazarian, Vahe (Student's Journal of Health Research Africa, 2025)
Gastric cancer is a major global health concern, ranking as the fifth most commonly diagnosed cancer and a leading cause of mortality, often detected at advanced stages. It's a multifactorial disease influenced by genetics, H. pylori infection, environmental factors, and diet, predominantly affecting older men. Approximately 90% are adenocarcinomas, characterized by specific molecular biomarkers. Diagnosis primarily relies on EGD with biopsy. Historically, treatment involved surgery and chemotherapy, but the field is rapidly evolving towards targeted and immunotherapies. Crucially, the CRISPR-Cas9 gene editing system has emerged as a promising tool with the potential to precisely modify genes involved in gastric carcinogenesis, offering novel therapeutic avenues. This narrative review highlights that gastric cancer remains a major global health challenge, driven by multifactorial risk factors including H. pylori infection, dietary habits, and genetic predispositions, often presenting with non-specific symptoms that lead to late diagnosis. While diagnostic tools have advanced from EGD to AI-assisted endoscopy, and TNM staging has been refined, molecular heterogeneity necessitates the integration of biomarkers for personalized approaches. Therapeutically, management has evolved significantly, encompassing perioperative chemotherapy and surgical techniques (from endoscopic resections to D2 lymphadenectomy), increasingly integrating targeted therapies (like HER2 inhibitors) and immunotherapies for advanced disease. Crucially, emerging CRISPR-Cas9 gene editing technology shows immense promise for future therapeutic interventions, aiming to address genetic drivers of carcinogenesis and further revolutionize patient outcomes. Hence, gastric cancer remains a significant global health challenge, with its complex nature (risk factors, symptoms, and diagnosis) necessitating a continuous evolution in its management. Advancements in diagnostic tools, refined staging, and the integration of molecular insights are driving personalized treatments, while CRISPR-Cas9 gene editing holds transformative potential for future therapies.